Apakah Size, Profitabilitas dan Debt To Equity Ratio Berpengaruh Terhadap Ketepatwaktuan Pelaporan Keuangan Perusahaan? - Suheny Anugrah Bijaksani Bugis; Adi Prasetyo; Tri Wahyu Oktavendi (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to analyze the effect of company size, profitability and debt to equity ratio on the timeliness of corporate financial reporting. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2017. The sampling technique used is purposive sampling. Samples that met the criteria in this study were 140 companies. The method of data analysis uses logistic regression. The results prove that the size of the company tends to affect the timeliness of corporate financial reporting, profitability tends to affect the timeliness of corporate financial reporting, while the debt to equity ratio tends not to affect the timeliness of corporate financial reporting.